Representasi Depresi dan Kehilangan Makna Diri dalam Lirik Lagu “Ba'ad Gheyabo” Karya Ahmed Batshan Kajian PsikologiSastra - Nursukma suri; Nur Asiyah Batubara; Riri Apsari; Siti Onur Hasibuan (Hijai - Journal on Arabic Language and Literature, 2026)
This study explores how Ahmed Batshan's song "Ba'ad Gheyabo" depicts despair and meaninglessness. It focuses on how depressive symptoms are depicted and how a loss of self-meaning is reflected in the lyrical structure and diction. The World Health Organization's assessment on the growing global concern over depression and the paucity of research on depression in modern Arabic music lyrics are the driving forces for the study. Based on Sigmund Freud's psychoanalytic theory, this study uses a descriptive qualitative methodology with a focus on the id, ego, and superego. Lyrics from songs were gathered using note-taking methods and library research. Miles, Huberman, and Saldaña's interactive model is used in the analysis. The results demonstrate that an imbalance in the personality structure is the root cause of depression. The ego is unable to deal with reality, the superego exacerbates pressure and guilt, and the id reflects strong feelings and a fixation with loss. Melancholia, which stands for depression and a crisis of meaning, is the result of this disorder.